Lukurmata : household archaeology in prehispanic Bolivia - Bermann, Marc, 1960- (Princeton legacy library, 1994)
"Comparison of 'capital-centric' and local household perspectives using a 1,500-year-long chronology of pottery, artifacts, and architecture at Lukurmata identifies Tiwanaku as a State rather than a trade or religious network. The greatest changes occurred in shape, size, layout, and diversity of household buildings; domestic pottery remained relatively stable"--Handbook of Latin American Studies, v. 57.